The Application of Equity in Brazilian Court Decisions during the Covid-19 Pandemic: Are there any Obstacles? - Anna Lucia Berardinelli (Faculty of law Udayana University, 2020)
Brazil follows the precepts of the Civil Law system that leaving only limited space for equity. The ongoing pandemic spread crisis and uncertainty worldwide, and there is not enough time for legislators to fill the gaps. Even the already existing legal provisions were designed to cope with unexpected situations, they might be inappropriate in such an unprecedented situation, where everyday contracts are cancelled, obligations are defaulted, companies are bankrupt, and individual rights are mitigated. Courts in Civil Law countries usually do not allow to ground their decisions exclusively on equity powers. This article aims to discuss and propose how the use of evaluative equity in judicial decisions could be the path in the search for the realization of justice, through not only its integrative function but also in an evaluative way, ensure justice in the concrete case. This article concludes that equity is an essential tool for achieving a fair decision and the demands for the common good.